Potensi jerami sebagai pakan ternak ruminansia - yanuartono - yanuartono; Hary Purnamaningsih; Soedarmanto Indarjulianto; Alfarisa Nururrozi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The basic reason for poor performance of livestock in developing countries, include Indonesia,  is qualitative fluctuations in feed. Therefore knowledge in utilizing agroindustry byproduct as feedstuff to meet nutrient requirement of animals is important. Rice straw is a crop residue of rice production and can be used as a feed for ruminants because it is easily and cheaply available in many Asian countries. Rice straws have low nutritive value and it is generally limited by several factors such as the low nutritional quality due to high fiber content and lignification process. In Indonesia, rice straw has been widely utilised in livestock feeding systems, thus the need to improve them is imperative as they are an abundant crop residue. Much more attention has been paid to improving its feeding value in order to increase livestock productivity. Many processing methods to improve the nutritive value of rice straw have been investigated. These methods can be classified as physical, chemical or biological. Usually, processing methods improves the nutritive value of straw by increasing its digestible energy content, by increasing feed intake, or by a combination of the two. This paper aims to examine the potential of rice straw as basal feed livestock as well as efforts to improve their nutritional value.Key words: livestock, rice straw, processing methods, nutritional value